Influence of Ti atoms on the magnetic order in quaternary NiMnGe:Ti compounds. (2nd November 2018) - Penc, Bogusław; Hoser, Andreas; Baran, Stanisław; Duraj, Ryszard; Marzec, Monika; Jaworska-Gołąb, Teresa; Szytuła, Andrzej; Dyakonov, Vladymir; Nedelko, Natalia; Sivachenko, Aleksandr; Dyakonov, Konstantin; Bażela, Wiesława; et al.
ABSTRACT: The NiMn0.95 Ti0.05 MnGe and Ni1– x Ti x MnGe ( x = 0.05, 0.15 and 0.25) compounds have been studied by X-ray (at room temperature), neutron diffraction (2–360 K), DSC (130–390 K) and magnetic studies (2–350 K). The compounds with a low Ti concentration exhibit an orthorhombic crystal structure of NiTiSi-type (space group Pnma), whereas those with a large Ti content exhibit a hexagonal Ni2 In-type structure (space group P63 /mmc). The compounds with x = 0.05 are antiferromagnets with the helicoidal magnetic structure. The samples with the hexagonal crystal structure have a noncollinear magnetic structure with antiferro- along a -axis and ferro- along c -axis components. The obtained magnetic entropy change( Δ S M max ) has the maximum value equal to 6.2 J/kgK at T = 200 K and H = 90 kOe for Ni0.85 Ti0.15 MnGe. For compounds with x = 0.05, 0.15 and 0.25, the magnetic ( P, T ) phase diagrams, under hydrostatic pressure up to 12 kbar, were determined.